Strategi Pembinaan Dalam Membangun Resiliensi Anak Berkonflik dengan Hukum Di Lembaga Pembinaan Khusus Anak (LPKA) Kelas I Kutoarjo - Alfina Ananda Putri; Theofilus Apolinaris Suryadinata (Dimensia: Jurnal Kajian Sosiologi, 2026)
The number of children in conflict with the law (CICL) continues to rise, with 1,639 children recorded as detainees in 2024 and 140 undergoing rehabilitations at the Class I Juvenile Correctional Institution (LPKA) Kutoarjo as of January 2025. This study aims to analyze rehabilitation strategies for building resilience among CICL, identify implementation challenges, and explore their adaptation processes during mentoring. Using a qualitative case study approach and Pierre Bourdieu’s theory of social practice (habitus, capital, and field), the research finds that the rehabilitation strategy at LPKA Kutoarjo is implemented through maximum, medium, and minimum-security stages. This strategy functions as a social practice that strengthens CICL’s resilience through access to social, economic, and cultural capital. The mentoring process also helps shape a new habitus aligned with institutional norms and prepares CICL for reintegration into society. Overall, the strategy plays a vital role in fostering sustainable resilience among children in conflict with the law.